Evaluation of the damage by the coffee berry borer Hypothenemus hampei in the first stages of development of the coffee fruit - MENDOZA-HERNÁNDEZ, MILTON EMIRO; GÓMEZ-MUÑOZ, CARLOS ENRIQUE; BAENA-GARCÍA, DIOSDADO (Revista Colombiana de Entomología, 1997)
This work had as objetive to evaluate the damage caused by the coffeeberry borer Hypothenemus hampei Ferrari, in the firsts stages of development, as well as to establish the functional relationship between the Percentage of "Garrapata" grain Fall (until 90 days after blooming), and the infestation level of the pest, in two coffee arcas from Valle del Cauca Department, Colombia. The work was carried out between may of 1995 and January of 1996, in 4 farms from El Cerrito (Low Marginal Zone, less than 1300 m.a.s.l. of altitude) and 8 farms of Palmira and Yotoco (Optimum Zone, between 1300 and 1800 m.a.s.l. of altitude). During 26 weeks 5507 evaluations were recorded between both zones. A damage caused to adult borer, don’t report in the literature until this moment. This occurred of natural manner and it consists that the insect makes a perforation in the blossoms base, fading the same, to observe then their fall. Resulting, branches without or few grains production. It was concluded, that in natural conditions, only a relatively low part (1.6% in optimum zone and 3.1% in low marginal zone) of the total garrapata fruits, are to fall by the action of different factors such as: borers, adverse climatic conditions (rainfall, temperature. relative humidity), soil, management of the cultivation, etc. Comparing the coffee zones studied, each 1% of the increase in the infestation level, in the percentage of garrapata grain fall because of borer there was 0.47% increase in the optimum zone, and of 0.26% in the low marginal zone having there validity for the infestation level ranges established (0% to 10.7% zone in the optimum and 0% to 23%, in the low marginal zone we found adult females boring the flower buds and causing flower dropping, which produced branches without berries). The garrapata grain fall percentage due to different factors, such as adverse climatic conditions, soil, management of the cultivation, etc, represented a 0.195% in optimum zone and a 0.544% in low marginal zone. The percentage of green coffeeberry holed .by the borer at the beginning of the fructification (first 26 weeks), explains the garrapata grain fall percentage at the beginning in a 95% for optimum zone and in a 91 % for low marginal zone, with a confidence level of 99% in both cases.